Cervical Intradural Extramedullary Melanocytoma , Associated with Nevus of Ito. Recurrence and Long-Term Outcome - Tamimi, Ahmad; obeidat, Fatimah N; Al Ryalat, Nosaiba T; Juweid, Malik E.; Jabaiti, Samir; Olimat, Yazen; Doudeen, Rahma M.; Almustafa, Sahar; Abuajamieh, Zaid; Ftaiha, Majed; et al. (Jordan Medical Journal, 2023)
Background: Melanocytoma is a rare pigmented central nervous tumor. In the spine, it may develop in meninges, extramedullary or intramedullary. It usually has good outcome after total excision. Case report: A 40-year-old male patient was admitted to our hospital 12 years ago with a 3-month history of progressive neck pain and difficulty walking. On clinical examination, he showed upper dorsal bilateral gray blue hyperpigmentation, quadriparesis and bilateral hypoesthesia below C4. Cervical magnetic resonance imaging (MRI) T1-weighted images without contrast showed a C3-C4 intradural, extramedullary lesion. The patient underwent total microsurgical resection of the lesion. Histological and immunohistochemical analyses confirmed the diagnosis of melanocytoma. Another skin biopsy of the abnormal area showed histological findings of a blue skin nevus. Eight years after resection the patient presented with recurrent symptoms, which were similar to his initial presentation. Cervical MRI showed an intradural extramedullary tumor anterior to the spinal cord at the same C3-C4 level. The patient underwent a second complete tumor excision and melanocytoma was confirmed histologically. The patient significantly improved and remained well at last follow-up. Conclusions: Intradural extra- or intramedullary melanocytoma is a rare benign tumor that frequently recurs but usually has good outcome following total excision. Keywords: Spinal cord, Meningeal, Melanocytoma, Extramedullary, Skin Nevus of Ito, Outcome